2022
DOI: 10.3389/fphar.2022.903699
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of RNA Methylation Modification in Colorectal Cancer

Abstract: Accumulating evidence indicates that RNA methylation, as the most common modification of mRNA, is of great significance in tumor progression and metastasis. Colorectal cancer is a common malignant tumor of the digestive system that seriously affects the health of middle-aged and elderly people. Although there have been many studies on the biological mechanism of the occurrence and development of colorectal cancer, there are still major deficiencies in the diagnosis and prognosis of colorectal cancer. With the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 109 publications
1
4
0
Order By: Relevance
“…It is important to highlight that the results in tissues agreed with those previously reported by other authors who found increased m6A methylation in miRNA let-7a in pancreatic and CRC tissues compared to paired normal tissue samples using a nontargeted mass spectrometry sequencing technique . These results also agree with reports claiming increased m6A levels in total RNA extracted from CRC cells and tissues through the upregulation of the methyltransferase METTL3, which also promotes metastasis of CRC, , and with the analysis of m6A-related RNAs other than miRNAs as prognostic factors in CRC . Furthermore, the results obtained in the determination of total miRNA let-7a in cultured cancer cells and tissues (Figure a,d) also agree with the downregulation of this miRNA in CRC tissues ,, and the accumulating evidence indicating that let-7 miRNAs function as a tumor suppressor in CRC .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It is important to highlight that the results in tissues agreed with those previously reported by other authors who found increased m6A methylation in miRNA let-7a in pancreatic and CRC tissues compared to paired normal tissue samples using a nontargeted mass spectrometry sequencing technique . These results also agree with reports claiming increased m6A levels in total RNA extracted from CRC cells and tissues through the upregulation of the methyltransferase METTL3, which also promotes metastasis of CRC, , and with the analysis of m6A-related RNAs other than miRNAs as prognostic factors in CRC . Furthermore, the results obtained in the determination of total miRNA let-7a in cultured cancer cells and tissues (Figure a,d) also agree with the downregulation of this miRNA in CRC tissues ,, and the accumulating evidence indicating that let-7 miRNAs function as a tumor suppressor in CRC .…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, N 6 -methyladenosine (m6A) in RNA, considered the most abundant RNA methylation (∼50% of total methylated ribonucleotides), is a dynamic and reversible modification mediated by writer (m6A-methyltransferases), removed by eraser (demethylases), and recognized by reader (m6A-binding) proteins. The m6A RNA methylation is widely found in mRNAs and long noncoding RNAs (lncRNAs), and recent evidence suggests its role in variety of cancers, including CRC development, carcinogenesis, progression, and therapeutics. , …”
mentioning
confidence: 99%
“…Elevated blood levels of N2,N2-dimethylguanosine and pseudouridine among patients with acute leukemia and breast cancer were first reported more than four decades ago 14 . This initial finding has been followed by a number of studies linking these two nucleosides and cancer, including colorectal cancer 15 , ovarian cancer 16 , and prostate cancer 17 . Recent studies extended these findings by showing that N2,N2-dimethylguanosine was also associated with high BMI 18 .…”
Section: Discussionmentioning
confidence: 96%
“…Colon adenocarcinoma (COAD), one of the most common malignancies, is among the top five in terms of morbidity and death from tumor-related illnesses [1][2][3][4]. Predictions indicate that in 2022, colorectal cancer (CRC) diagnoses will number 600,000 in China and 160,000 in the US, with 300,000 and 55,000 cases of CRC-related deaths in each country, respectively [5].…”
Section: Introductionmentioning
confidence: 99%